Beam selection for stereotactic ablative radiotherapy using Cyberknife with multileaf collimation. (February 2019) - Bedford, James L.; Ziegenhein, Peter; Nill, Simeon; Oelfke, Uwe
Highlights: A fast optimisation framework is used to create IMRT SABR plans for Cyberknife. The value of the Cyberknife multileaf collimator is investigated. A beam selection algorithm is used to determine a subset of beam orientations. Fifteen selected beams are sufficient to create high-quality treatment plans. Treatment time is minimised using this approach. Abstract: The Cyberknife system (Accuray Inc., Sunnyvale, CA) enables radiotherapy using stereotactic ablative body radiotherapy (SABR) with a large number of non-coplanar beam orientations. Recently, a multileaf collimator has also been available to allow flexibility in field shaping. This work aims to evaluate the quality of treatment plans obtainable with the multileaf collimator. Specifically, the aim is to find a subset of beam orientations from a predetermined set of candidate directions, such that the treatment quality is maintained but the treatment time is reduced. An evolutionary algorithm is used to successively refine a randomly selected starting set of beam orientations. By using an efficient computational framework, clinically useful solutions can be found in several hours. It is found that 15 beam orientations are able to provide treatment quality which approaches that of the candidate beam set of 110 beam orientations, but with approximately half of the estimated treatment time. Choice of an efficient subset of beam orientations offers the possibility to improve the patient experience and maximise the number of patients treated.